An optimized, sensitive and stable reduced graphene oxide-gold nanoparticle-luminol-H2O2 chemiluminescence system and its potential analytical application - 王闻硕 何大伟 王继红 段嘉华 彭洪尚 吴洪鹏 富鸣 王永生 张希清 (中国物理B：英文版, 2014)
The chemiluminescence （CL） performance of luminol is improved using reduced graphene oxide/gold nanoparticle （rGO-AuNP） nano-composites as catalyst. To prepare this catalyst, we propose a linker free, one-step method to in- situ synthesize rGO-AuNP nano-composites. Various measurements are utilized to characterize the resulting rGO-AuNP samples, and it is revealed that rGO could improve the stability and conductivity. Furthermore, we investigate the CL signals of luminal catalyzed by rGO-AuNP. Afterwards, the size effect of particle and the assisted enhancement effect of rGO are studied and discussed in detail. Based on the discussion, an optimal, sensitive and stable rGO-AuNP-luminon- H202 CL system is proposed. Finally, we utilize the system as a sensor to detect hydrogen peroxide and organic compounds containing amino, hydroxyl, or thiol groups. The CL system might provide a more attractive platform for various analytical devices with CL detection in the field of biosensors, bioassays, and immunosensors.